2020
DOI: 10.1097/scs.0000000000006401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Success Rate of Dental Implants Placed in Autogenous Bone Graft Regenerated Areas and Pristine Bone

Abstract: Autogenous bone grafting still has been considered as the “gold standard” and wildly used in the case of alveolar bone reconstruction. The aim of the present study is to evaluate the success rate of implants placed in autogenous block augmented ridges and implants placed in pristine bone (PB). This study included 113 patients. Fifty-three patients were treated with autogenous block grafts and particulate bone, after 6 months of healing implant placements were performed in autogenous bone augmented (ABA) areas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The authors concluded that FFBA does not represent a safe alternative to AUBB [128], which they substantiated by a further study with corresponding results [128]. An implant survival rate of 100% was reported for implants inserted into both cortical AUBB and cortico-cancellous FFBA blocks applied for horizontal bone augmentations in two separate studies by the same authors [34,103], which emphasizes the feasibility of achieving similar results with AUBB and ALBB following the regeneration of horizontal bone defects. An ISR of 100% for both cohorts was reported by all comparative studies on AUBB and processed allogeneic bone blocks.…”
Section: Implant Survival Ratementioning
confidence: 93%
See 2 more Smart Citations
“…The authors concluded that FFBA does not represent a safe alternative to AUBB [128], which they substantiated by a further study with corresponding results [128]. An implant survival rate of 100% was reported for implants inserted into both cortical AUBB and cortico-cancellous FFBA blocks applied for horizontal bone augmentations in two separate studies by the same authors [34,103], which emphasizes the feasibility of achieving similar results with AUBB and ALBB following the regeneration of horizontal bone defects. An ISR of 100% for both cohorts was reported by all comparative studies on AUBB and processed allogeneic bone blocks.…”
Section: Implant Survival Ratementioning
confidence: 93%
“…The survival of implants within grafting materials is probably the most crucial analysis, because the main purpose of bone grafting procedures is dental rehabilitation, which should last decades, and ideally, a lifetime. As for AUBB, two studies reported implant survival rates (ISRs) below 80% for cortico-cancellous iliac grafts with simultaneous [34] and delayed implants [74] in the maxilla, and both studies included totally edentulous patients. Both authors reasoned the loss of implants with marginal bone resorption, which was demonstrated to be increased within the first three years.…”
Section: Implant Survival Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Maxillary sinus floor augmentation (MSFA) surgery with simultaneous or deferred placement of implants is a highly predictable surgical technique in cases of atrophic posterior maxilla [ 1 ], allowing implant-supported rehabilitation in cases where there would otherwise be insufficient remaining bone substrate for implant placement. MSFA achieves implant survival rates similar to those achieved in pristine bone [ 2 , 3 ]. During this surgical procedure, perforations of the sinus membrane may occur due either to iatrogenic causes derived from incorrect surgical handling or to anatomical considerations inherent to the individual patient, which can make the procedure difficult [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 94%
“…Autografts are often used in more complex cases and are associated with low risk of graft rejection or infection. 5 Allografts: Allografts are bone graft materials sourced from human donors, typically from cadavers. These grafts are processed and sterilized to remove cellular components while retaining the bone matrix.…”
Section: Types Of Bone Graft Materials In Dentistrymentioning
confidence: 99%